1975
DOI: 10.1254/jjp.25.25
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Beta-Adrenergic Receptor Blocking Agents on Blood Pressure in Conscious Hypertensive Rats

Abstract: Abstract-The effects of beta-adrenergic receptor blocking agents administered i.v. on the blood pressure in conscious spontaneously hypertensive rats (SHR), renal hyper tcnsive rats (RHR) and normotensive Wistar strain rats (NR) were studied. dl-Pro pranolol and dI-YB-2, I mg/kg i.v., caused a sustained rise in blood pressure in SHR and RHR.The maximum response of each beta-blocking agent after phentolamine, 10 mg/kg i.v., in SHR and RHR was significantly larger than that in NR. The po tency ratio for the hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…In mature spontaneously hypertensive rats, propranolol has been reported to lower (Roba, Lambelin & de Schaepdryver, 1972) or to have no effect on (Forman & Mulrow, 1974, Buniag, 1977 systolic BP, and to lower (Garvey & Ram, 1975) to raise (Nakao, Kato & Takagi, 1975) or to have no effect on (Weiss, Lundgren & Folkow, 1974;Conway, Darwin Hilditch, Loveday & Reeves, 1975) mean arterial BP. Furthermore, it has been found that pretreatment with propranolol may either not affect (Frohlich & Pfeffer, 1975) or may prevent (Weiss et al, 1975) the development of the spontaneous hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…In mature spontaneously hypertensive rats, propranolol has been reported to lower (Roba, Lambelin & de Schaepdryver, 1972) or to have no effect on (Forman & Mulrow, 1974, Buniag, 1977 systolic BP, and to lower (Garvey & Ram, 1975) to raise (Nakao, Kato & Takagi, 1975) or to have no effect on (Weiss, Lundgren & Folkow, 1974;Conway, Darwin Hilditch, Loveday & Reeves, 1975) mean arterial BP. Furthermore, it has been found that pretreatment with propranolol may either not affect (Frohlich & Pfeffer, 1975) or may prevent (Weiss et al, 1975) the development of the spontaneous hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Blood pressure and heart rate of spontaneously hypertensive rats (SHR) were measured according to the method described by Nakao et al (2 namoyl)reserpate (CD-3400), as shown in Fig. 1, is a light yellow powder which is in soluble in water and was crystallized from dioxane.…”
Section: Methodsmentioning
confidence: 99%
“…Although the spontaneously hypertensive (SH) rat has been used extensively to study the aetiology of hypertensive disease and to investigate the mechanisms responsible for mediating the effects of clinically useful anti-hypertensive drugs, it, like other laboratory animal preparations, has proved to be of limited value in studying the antihypertensive properties of,-adrenoceptor blocking drugs (see review by Buckingham & Hamilton, 1979). It is feasible that the ability of these drugs to stimulate adrenal catecholamine release (Nakano & Kusakari, 1965;Kayaalp & Kiran, 1966;Kayaalp & Turker, 1967;Dasgupta, 1968;Yamamoto & Sekiya, 1969;Regoli, 1970;Eliash & Weinstock, 1972;Regoli, Regoli & Gysling, 1972;Nakao, Kato & Takagi, 1975) could be responsible for masking their blood pressure lowering activity in conscious animals. In this respect, unilateral adrenalectomy and contralateral adrenal demedullation has been shown to unmask 0007-1188/80/040667-10 $01.00 a blood pressure lowering effect of oxprenolol in onekidney renal hypertensive rats (Brunner & Hedwall, 1970), and to augment the anti-hypertensive response to pindolol in deoxycorticosterone acetate (DOCA)/ saline-treated rats (Buckingham, Hamilton & Robson, 1978).…”
Section: Introductionmentioning
confidence: 99%